2016
DOI: 10.1093/gastro/gow033
|View full text |Cite
|
Sign up to set email alerts
|

Real world experience with pegylated interferon and ribavirin in hepatitis C genotype 1 population with favourableIL28Bpolymorphism

Abstract: Background and aim: Conventional hepatitis C treatment using pegylated interferon (PEG-IFN) and ribavirin is associated with significant side effects. IL28B polymorphism can predict response to treatment, with CC genotype having a better response. ITPA gene deficiency protects against clinically significant anaemia induced by treatment. The purpose of this study was to determine IL28B polymorphism and ITPA variation among hepatitis C genotype 1 patients who have undergone therapy with PEG-IFN and ribavirin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our results showed that there was a predominance (85.3% overall) of the favourable CC allele in these populations. Given our findings and the prohibitive cost of DAA agents, and keeping in mind that IL28B SNP is highly associated with increased sustained viral response following conventional PEG-IFN+RBV combination therapy for CHC, (8,(21)(22)(23)(24) it would seem reasonable to consider IL28B genotyping a priority, with the view of using PEG-IFN+RBV combination therapy as a first-line treatment for CHC, when appropriate, for a substantial proportion of the HCV-infected population in Singapore. Thus, the costly DAA agents can be reserved for the minority who have contraindications to, or poor predictive factors for sustained viral response following PEG-IFN+RBV combination therapy.…”
Section: Discussionmentioning
confidence: 88%
“…Our results showed that there was a predominance (85.3% overall) of the favourable CC allele in these populations. Given our findings and the prohibitive cost of DAA agents, and keeping in mind that IL28B SNP is highly associated with increased sustained viral response following conventional PEG-IFN+RBV combination therapy for CHC, (8,(21)(22)(23)(24) it would seem reasonable to consider IL28B genotyping a priority, with the view of using PEG-IFN+RBV combination therapy as a first-line treatment for CHC, when appropriate, for a substantial proportion of the HCV-infected population in Singapore. Thus, the costly DAA agents can be reserved for the minority who have contraindications to, or poor predictive factors for sustained viral response following PEG-IFN+RBV combination therapy.…”
Section: Discussionmentioning
confidence: 88%
“…This has raised a global discussion among competing health priorities, regarding the unrestricted access of all patients to new therapies. It has been suggested to consider IFN-based regimens as valuable treatment of HCV patients with favorable genotypes of IL28B, who are still unable to afford the newer DAAs, especially in resource-limited Asian countries where favorable genotypes of IL 28B is highly prevalent [18].…”
Section: Introductionmentioning
confidence: 99%
“…The use of IL2BB polymorphism is mentioned as a "viable treatment option", and this has been studied in our group previously. (6) Yours sincerely,…”
mentioning
confidence: 96%